Two new feather mite species of the family Analgidae (Acariformes: Analgoidea) from the Rufous-collared Sparrow Zonotrichia capensis (Müller, 1776 (Passeriformes: Passerellidae) - Pedroso, Luiz Gustavo A.; Hernandes, Fabio Akashi (Zootaxa, 2018)
Two new feather mite species of the family Analgidae are described from the Rufous-collared Sparrow, Zonotrichia capensis (Müller, 1776) (Passeriformes: Passerellidae), from Brazil: Analges ticotico sp. nov. (Analginae) and Strelkoviacarus brasiliensis sp. nov. (Anomalginae). Analges ticotico sp. nov. is characterized by the heteromorphic males having three short and rounded spines on the inner margin of femur III, the anterior margin of adanal shield convex, the hysteronotal shield with the anterior margin sinuous, and the terminal lamella rectangular. Strelkoviacarus brasiliensis sp. nov. is characterized by the anterior ends of the adanal shields being convergent and encompassing the bases of setae ps3 in males, and by the strongly convex median extension of the prodorsal shield and short dorsal setae vi, c2, d2 and e2 in females. These species represent the first records of corresponding feather mite genera in Brazil.